Acute unilateral vestibular neuritis contributes to alterations in vestibular function modulating circumvention around obstacles: A pilot study suggesting a role for vestibular signals in the spatial perception of orientation during circumvention - Allum, John; Rust, Heiko Mario; Honegger, Flurin (Frontiers in Integrative Neuroscience, 2022)
BACKGROUND: Walking among crowds avoiding colliding with people is described by vestibular deficit patients as vertigo-inducing. Accurate body motion whilst circumventing an impeding obstacle in the gait pathway is dependent on an integration of multimodal sensory cues. However, a direct role of vestibular signals for spatial perception of distance or orientation during obstacle circumvention has not been investigated to date. METHODS: We examined trunk yaw motion during circumvention in patients with acute unilateral vestibular loss (aUVL), and compared their results with age-matched healthy controls (HCs). Subjects performed 5 gait tasks with eyes open twice: walk 6m in total, but after 3m, circumvent to the left or right as closely as possible a cylindrical obstacle representing a person, then veer back to the original path; walk 6m but after left and right circumvention at 3m veer, respectively, to the right, and left 45 deg; and walk 6m without circumvention. Trunk yaw angular velocities (YAV) were measured with a gyroscope-system. RESULTS: YAV peak amplitudes approaching to and departing from the circumvented object were always greater for aUVLs compared to HCs, regardless of whether passing was to the aUVLs’ deficit or normal side. The departing peak YAV was always greater, circa 52 and 87%, than the approaching YAV for HCs when going straight or veering 45 deg (p≤0.0006), respectively. For aUVLs departing velocities were marginally greater (12%) than approaching YAVs when going straight (p<0.05) and were only 40% greater when veering 45 deg (p=0.05). The differences in departing YAV resulted in significantly lower trajectory-end yaw-angles for veering trials to the deficit side in aUVLs (34 vs 43 degs in HCs). CONCLUSIONS: These results demonstrate the effects of vestibular loss on yaw velocity control during the 3 phases of circumvention. Firstly, approaching an obstacle, greater YAV is programmed in aUVLs. Secondly, the departing YAV is programmed to be less than HCs with respect to the approaching velocity resulting in larger deficit side passing yaw angles. Thirdly, UVLs have yaw errors returning to the desired trajectory. These results could provide a basis for rehabilitation protocols helping to avoid collisions while walking in a crowded space.